Interesno ravnotežje med zastaviteljem in zastavnim upnikom v rimskem pravu - Žepič, Vid (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2022)
The Roman hypotheca, unless agreed otherwise, originally bestowed upon the creditor (pledgee) merely a claim to transfer the pledged object into his possession, when the payment was due. Owing to the weak protection, the creditor strived to strengthen his pecuniary interests by supplementary covenants. To prevent abuses by the economically and socially superior creditor, the classical jurists sought to attain a balance of interests of the contracting parties. The fundamental elements of their effort were the recognition of pledgee’s right of sale as an essential element of the pledge contract on the one hand, and the recognition of the pledgor’s right to the surplus of purchase price on the other. Kaser’s thesis that the Roman pledgee enjoyed a particularly strong legal position as a distinctive character of Roman law has been proved to be an exaggeration even in the light of the development of classical law. In the post-classical period, a shift towards prioritising the position of the pledgor is noticeable. It corresponds to a general tendency of post-classical law to favour the debtor as a stereotypically weaker party. Among the innovations of the period, the limitations regarding the object of the pledge were introduced, new interpretative approaches concerning the pledge of the increments were accepted, lex commissoria was entirely prohibited, the creditor’s discretion over the realisation of the pledge was restricted, and the State’s control over the sale of the object of pledge was strengthened. The protective safeguards established through imperial legislation can be seen as a symptom of the declining economy and although they improved the pledgor’s social standing, they reduced the supply of the credit.
Keywords: obligacijska razmerja; obligacijsko pravo; Pravna zgodovina; rimsko pravo; upniki; zastavna pravica